Trend and variability of NDVI of the main vegetation types in the Cape Region of Baja California Sur - Daniela Maldonado-Enríquez; Alfredo Ortega-Rubio; Aurora Margarita Breceda-Solís Cámara; Sara Cecilia Díaz-Castro; Joaquín Sosa-Ramírez; Raúl Octavio Martínez-Rincón (Revista Mexicana de Biodiversidad)
The Cape Region (CR) of Baja California Sur is located in the southernmost tip of the Baja California peninsula, Mexico. The vegetation of this region is dominated by scrubland (SRB) and tropical dry forest (TDF), but oak (OW) and oak-pine woodland (OWP) are also found in Sierra La Laguna Biosphere Reserve. These vegetation types, in this relatively small area, make the CR a contrasting and highly biodiverse region. This research used the Normalised Difference Vegetation Index (NDVI) to describe spatiotemporal variability of the vegetation cover in the CR. The analysed NDVI data derived from Landsat 7 during the growing season (September-November) from 2001-2015. Its spatial distribution showed the highest values in the TDF, OW and OPW. Higher variability was observed in SRB. Temporal variations of the annual NDVI mean of the growing season fluctuated in a range from 0.292 to 0.522, and with the highest values in 2014 while the lowest were observed in 2011. A general increasing trend was observed for the growing season over the period 2001-2015 for all analysed vegetation types. Remote sensing change detection methods combined with Geographic Information Systems, suggested that the vegetation of the area was well conserved during the period of study.